Routine antenatal syphilis screening In South West Nigeria- a questionable practice (2010)
Backgroud: Untreated maternal syphilis is strongly associated with adverse birth outcomes, especially in women with high titre syphilis. The WHO recommends routine serological screening in pregnancy. Some workers have advised a reappraisal of this practice, having demonstrated low sero-prevalence in their antenatal population. In view of this, the aim of this study was to determine the seroprevalence of syphilis in the antenatal population presenting at a major hospital in south-west Nigeria. Methods: This was a cross sectional study of healthy pregnant Nigerian women attending Adeoyo Maternity Hospital in the capital of Oyo State. The case record of every pregnant woman presenting for their first antenatal clinic visit over a 4-month period (September 1st to December 31st 2006) was reviewed. Results: During the study period, two thousand six hundred and seventy-eight women sought antenatal care. Three hundred and sixty-nine women (369; 13.4%) had incomplete records and were excluded from analysis. The records of the 2,318(86.6%) women with adequate records were subsequently reviewed. The mean age of the women was 27.4 years (± 5.34) and the mean gestational age 26.4 weeks (±6.36). The modal parity was 0. Only three patients were found to be reactive for syphilis giving a prevalence of 0.13%. Conclusion: The sero- prevalence value in this study is quite low and may justify the call to discontinue routine antenatal syphilis screening. However, a more rigorous screening program using diagnostic tests with higher sensitivity maybe necessary before jettisoning this traditional aspect of antenatal care.